Analysis ofindustrial and innovative developmentof the economyof Kyzylorda region (Journal of Economic Research & Business Administration, 2016)
Given the importance ofinnovation developmentin this case, primary processing and storage of agricultural products, fuel and energy complex, chemical and petrochemical industry, production of new materials, com munications, transport and communications,innovative projects inareas such asbiotechnology,forKyzylorda regionplays a special role.Creation ofinnovative businesses isdue tomanydifferentreasons.Internal causes directly related toentrepreneurial curiosity, pursue the goal of creating newproducts and technologies;the newexpansion of the range; increase in sales volume; the creationof the “innovator”, etc. External causesreflect themoodof the environment,that is, thetendencyof transformationinto a newtype of entrepreneur.